Optimization And Execution Of Multiple Holes-Drilling Operations Based On STEP-NC - Yusof, Yusri; Latif, Kamran; Hatem, Noor; A. Kadir, Aini Zuhra; Abedlhafd, Mohammed M. (Springer Science and Business Media Deutschland GmbH, 2021)
Modern computer numerical control (CNC) is intended to be more flexible, interoperable, adaptable, open, and intelligent. An open CNC control system was developed by added optimization feature in order to create high flexibility, affordable, and fast for STEP-NC drilling applications. Optimization of tool path operation can lead to a significant reduction in non-productive machining time. The newly developed system combines between open CNC control system and ant colony optimization (ACO) algorithm by using LabVIEW software. A developed system is based on STEP-NC interpretation, optimization, 3D simulation, and automatic document generation modules that have been used to verify and validate the system in extract and optimize STEP-NC drilling codes. The percentage of tool path improvement was 16.96%. This experimental study will fulfill the design of an open architecture CNC control system, optimize the CNC movement, and simulate and generate a document of the result.